2003
DOI: 10.1046/j.1365-2311.2003.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Are honey bees' foraging preferences affected by pollen amino acid composition?

Abstract: Abstract.  1. Although pollen is a vital nutritional resource for honey bees, Apis mellifera, the influence of pollen quality on their foraging behaviour is little understood. 2. In choice‐test experiments, bees showed no innate pollen‐foraging preferences, but preferred oilseed rape Brassica napus pollen over field bean Vicia faba pollen after previous foraging experience of oilseed rape. 3. The free amino acid content of oilseed rape and field bean pollen was compared using high‐performance liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
181
1
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(194 citation statements)
references
References 17 publications
3
181
1
9
Order By: Relevance
“…Despite the importance of P:L ratios, other components in pollen, such as micronutrients or individual amino or fatty acids, may still influence bee foraging decisions (45)(46)(47). Indeed, pollenkitt, which includes free fatty and amino acids that vary among pollen species, is critical for pollen recognition and phagostimulation (34-36, 48, 49).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of P:L ratios, other components in pollen, such as micronutrients or individual amino or fatty acids, may still influence bee foraging decisions (45)(46)(47). Indeed, pollenkitt, which includes free fatty and amino acids that vary among pollen species, is critical for pollen recognition and phagostimulation (34-36, 48, 49).…”
Section: Discussionmentioning
confidence: 99%
“…the quality and quantity of nectar provided to honeybees and its accessibility. In the following discussion we will focus on nectar resource because it is involved in honey production and has economic implications even if pollen quality may also influence sunflower attractiveness (Cook et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Here is presented a first step to investigate this potential using an original method based on the study of honeybee attendance during flowering period. Attendance, or the number of bee visits on the crop can be considered as an integrative parameter because social bees foraging preferences take in account nectar secretion and pollen quality and resource accessibility (Atlagić et al, 2003;Cook et al, 2003;Cnaani et al, 2006;Tepedino and Parker, 1982).…”
mentioning
confidence: 99%
“…Honeybees are broad polylectic insects (Cane and Sipes, 2006) and several authors have showed their preferences to specific taxa (Boelter and Wilson, 1984;Page et al, 1995;Currie, 2001, 2002;Cook et al, 2003;Pankiw et al, 2002). Although honeybees collect pollen from a relative small number of taxa compared to the number of plants growing around the colony, they usually prefer to collect pollen from plants that are in large populations (Severson and Parry, 1981;Coffey and Breen, 1997;Andrada and Telleria, 2005;Dimou and Thrasyvoulou, 2007;Avni et al, 2009).…”
Section: Discussionmentioning
confidence: 99%